Job satisfaction of music conductors and its relationship with motivation among members of youth music ensembles in Spain - Salvador Oriola Requena; Diego Calderón Garrido; Josep Gustems Carnicer (Per Musi, 2023)
The present research aims to know the professional burnout of the young musical ensemble conductors (bands and choirs) in Spain and if there is any relationship between the burnout and the motivation of their students. For this, a non-experimental exploratory descriptive study has been carried out consisting of the application of the Maslach Inventory on burnout and the MOT questionnaire on motivation to a sample of 20 directors and 660 members of several young bands and choirs, respectively. The results obtained show that conductors of young ensembles show low professional burnout and their students a high motivation, although some correlations and significant differences have been found in variables studied such as group type, conductor experience, etc.